Labor Market Dynamics: A Time‐Varying Analysis1. (5th March 2015) - Mumtaz, Haroon; Zanetti, Francesco
Abstract : This paper studies how key labour market stylized facts and the responses of labour market variables to technology shocks vary over the US postwar period. It uses a benchmark dynamic, stochastic, general equilibrium model enriched with labour market frictions and investment‐specific technological progress that enables a novel identification scheme based on sign restrictions on a SVAR with time‐varying coefficients and stochastic volatility. Key findings are: (i) the volatility in job finding and separation rates has declined over time, while their correlation varies across time; (ii) the job finding rate plays an important role for unemployment, and the two series are strongly negatively correlated over the sample period; (iii) the magnitude of the response of labour market variables to technology shocks varies across the sample period.